Sport public relations : managing stakeholder communication. - Stoldt, G. Clayton, ....-; Branvold, Scott E., ....-; Dittmore, Stephen W., ....- (Champaign : Human Kinetics, 2012)
Preface Acknowledgments Chapter 1: Introducing Sport Public Relations Definition of Sport Public Relations Characteristics of Sport Public Relations Sport Public Relations in Practice The Value of Public Relations Chapter 2: Integrating Public Relations with Strategic Management PR as a Strategic Management Tool Organizational Stakeholders and Constituents Issues Management Organizational Reputation Chapter 3: Creating Public Relations Campaigns Distinguishing Between Programs and Campaigns Planning and Executing Campaigns Working With Public Relations Firms Learning From Case Studies Chapter 4: Using the Internet in Sport Public Relations Evaluating Web Use in Sport PR Developing a Website Structuring Websites for Specific Stakeholders Identifying New Media Limitations and Problems Chapter 5: Developing Organizational Media Media Guides Other Organizational Media Electronic Organizational Media Corporate Communications Chapter 6: Focusing on the Sport Organization-Media Relationship Defining
Mass Media Mass Media Structures Relationship Between Mass Media and Sport Evolution of Sport PR Future of Sport PR Chapter 7: Managing the Sport Organization-Media Relationship Identifying Influential Media Serving Media at Organizational Events Developing a Media Policy Maximizing Media Exposure Chapter 8: Employing News Media Tactics News Releases Media Kits Social Media Releases Chapter 9: Staging Interviews, News Conferences, and Media Events Interviews News Conferences Media Days Chapter 10: Communicating in Times of Crisis Nature of Crises and the Need to Plan for Them Preparing for a Crisis Managing a Crisis Assessing a Crisis Response Chapter 11: Exploring Unmediated Communication Tactics Advantages of Unmediated Communication Tactics Results of Unmediated Communication Tactics Types of Unmediated Communication Activities Chapter 12: Demonstrating Social Responsibility Unique Aspects of CSR in Sport CSR Dimensions in Sport Planning CSR Programs Benefits of Demonstrating CSR A Final Word
Chapter 13: Communicating With Internal Publics Employee Relations Investor Relations Chapter 14: Communicating With External Publics Customer Relations Sponsor Relationship Management Donor Relations Government Relations Chapter 15: Legal and Ethical Dimensions of Sport Public Relations Legal Dimensions of Sport PR Ethical Dimensions of Sport PR Appendix A Selected Pages From a Media Guide Appendix B Sample Crisis Communication Plan Appendix C Community Relations Plan for a Minor League Baseball Franchise References Index About the Authors
Keywords: Public relations; Sport